Pengaruh Dana Alokasi Umum dan Dana Alokasi Khusus terhadap Belanja Modal dengan Pertumbuhan Ekonomi sebagai Variabel Moderasi di Kota Langsa - Tuti Meutia; Imelda Husna; Afrah Junita (Puslatbang KHAN, 2022)
This research was conducted to know the effect of the General Allocation Fund and the Special Allocation Fund on Capital Expenditures with Economic Growth as a Moderating variable. The results of this study indicate that: (1) General Allocation Funds have a positive and significant effect on Capital Expenditures (2) Special Allocation Funds have a positive and significant effect on Capital Expenditures (3) General Allocation Funds have no significant effect on Capital Expenditures with Economic Growth as a Moderating variable (4) Special Allocation Funds have a positive and significant effect on Capital Expenditures with Economic Growth as a Moderating variable (5) General Allocation Funds and Special Allocation Funds have a positive and significant effect on Capital Expenditures (6) General Allocation Funds and the Special Allocation Fund has a positive and significant effect on Capital Expenditure with Economic Growth as a Moderating variable.